Projected Land Use Change in an Oil-rich Landscape in Uganda: A Participatory Modelling Approach - Twongyirwe, Ronald; Fisher, Eleanor; Karungi, Christine; Ndugu, Nelson (The Extractive Industries and Society, 2022)
The discovery of oil in the North Albertine Rift Landscape of Uganda has increased pressure on land and heightened the potential for resource use conflict. In this article, we focus on changing land use dynamics as oil extraction unfolds in a new resource frontier. We ask how the development of the nascent oil industry will affect land use dynamics, including land use conflicts. This leads us to identify the land use change already arising and to use this as the basis for participatory modelling of projected change. Given they are dominant forms of land use, agriculture and forestry are central to our analysis. Design of the methodology combined remote sensing with innovative modelling incorporating participatory development methods. This facilitated insight into projected land use patterns, and specifically relationships between small-scale food production, commercial sugarcane production, and forestry conservation adjacent to settlement areas. Our data show that ill–defined land boundaries and an aggressive sugarcane out-grower scheme are avenues for so-called land grabbing. Modelling scenarios under both the status quo and under oil extraction suggest the land area covered by sugarcane production will increase at the expense of food crop farming. Given a context where forestry conservation is an important form of land use, we also consider the implications of local agricultural change on land reserved for conservation. Overall, our modelling indicates that in accounting for land use change within the resource frontier associated with oil extraction, there needs to be insight into the intricate interconnections between different forms of rural land use as future change unfolds. Understanding how oil extraction effects rural land use patterns holds relevance for planning in contexts of the Global South where new oil industries are emerging. Innovative methodologies for teasing out these complex land use dynamics can aid planning that seeks to anticipate and reduce land use conflict and support agricultural livelihoods.